Povezava med gibljivostjo in mišično togostjo na primeru zadnjih stegenskih mišic - Železnik, Petra (Šport (Ljubljana), 2023)
Flexibility is an essential component of physical fitness. It is affected by several factors, that can be divided into central and peripheral mechanisms. Peripheral mechanisms, among others, include muscle stiffness. Recently, ultrasound shear wave elastography has been established as a reliable method to assess muscle stiffness. In our study, we aimed to discern any potential correlation between the stiffness of hamstrings (assessed in relaxed position) and the range of motion in the hip and knee among healthy participants (n = 16). We employed ultrasound elastography to determine muscle stiffness and used the passive straight leg raise test (SLR) and active knee extension test (AKE) to assess flexibility. The results showed that there was no statistically significant correlation between the range of motion and biceps femoris stiffness (AKE: r = 0.02; p = 0.932; SLR: r = –0.06; p = 0.809) nor between the range of motion and semitendinosus muscle stiffness (AKE: r = –0.17; p = 0.536; SLR: r = –0.17; p = 0.536). The flexibility tests were in high positive correlation (r = 0.79; p < 0.001). Based on the results, we conclude that muscle stiffness assessed in relaxed position has a negligible effect on range of motion. We assume that flexibility is influenced by the stiffness of the muscles when stretched, the stiffness of surrounding non-muscular tissues and more importantly, by central mechanisms such as tolerance to stretch. Additional research is needed to confirm our assumptions and to explain the mechanisms underlying flexibility.
Keywords: elastografija; mišična togost; mišisce; obseg gibljivosti; stegenske mišice; šport